1999
DOI: 10.1002/(sici)1098-2779(1999)5:2<132::aid-mrdd7>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging and spectroscopy in PKU

Abstract: Phenylketonuria (PKU) is an autosomal recessive disorder that results in the accumulation of phenylalanine in the blood and soft tissues. Elevated levels of phenylalanine have neurotoxic effects on the developing brain, resulting in mental retardation. Early diagnosis and treatment limits the neurological damage. Magnetic resonance imaging (MRI) changes are seen in the white matter on T2 weighted imaging in many subjects. The severity of the changes do not correlate with clinical measures of neurological healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Magnetic resonance spectroscopy analysis showed that the highscoring patients had undetectable elevations of phenylalanine in the brain compartment, whereas the low-scoring subjects had pathological elevated phenylalanine levels in their brains [Weglage et al, 1998a]. Further studies in additional patients measured brain phenylalanine content and flux rates of phenylalanine at the blood brain barrier between vascular and brain spaces [Weglage et al, 1998b;Moller et al, 1998;Moats et al, 1999]; the latter corroborated the initial observations. The findings suggest an effect of allelic variation (perhaps polymorphic) on a high-Km L-type transporter for large neutral amino acids shared by phenylalanine.…”
Section: A Modi¢er Locus Acting As a ''Protector''mentioning
confidence: 78%
“…Magnetic resonance spectroscopy analysis showed that the highscoring patients had undetectable elevations of phenylalanine in the brain compartment, whereas the low-scoring subjects had pathological elevated phenylalanine levels in their brains [Weglage et al, 1998a]. Further studies in additional patients measured brain phenylalanine content and flux rates of phenylalanine at the blood brain barrier between vascular and brain spaces [Weglage et al, 1998b;Moller et al, 1998;Moats et al, 1999]; the latter corroborated the initial observations. The findings suggest an effect of allelic variation (perhaps polymorphic) on a high-Km L-type transporter for large neutral amino acids shared by phenylalanine.…”
Section: A Modi¢er Locus Acting As a ''Protector''mentioning
confidence: 78%
“…While this interpretation is tempting given that the majority of this population displays WMAs (Bick et al, 1991;Cleary et al, 1994;Pietz, Kreis et al, 1996;Thompson et al, 1993), most investigators believe that these white matter lesions have minimal, if any, adverse consequences (Cleary & Walter, 2001;Moats, Scadeng, & Nelson, 1999). This view is based on studies that have reported a non-significant relationship between WMAs and general intelligence (Bick et al, 1993;Pearsen, Gean-Marton, Levy, & Davis, 1990;Thompson et al, 1993;Weglage et al, 1995).…”
Section: White Matter Abnormalities (Wma)mentioning
confidence: 93%
“…While our rate of pathology was slightly below that reported in other studies (Bick et al, 1991;Cleary et al, 1994;Pietz, Kreis et al, 1996;Thompson et al, 1993), our sample was significantly younger. In the past this pathology has been considered to have minimal, if any, clinical significance (Cleary & Walter, 2001;Moats et al, 1999), however we propose that severity of pathology may need to reach a certain threshold before decrements in neuropsychological functioning are observable. When we differentiated the PKU group according to severity of WM pathology, we found that the group of children with abnormalities extending into subcortical and/or frontal regions (Moderate WMA group) exhibited significant impairments in attention, processing efficiency, memory and learning, and executive dysfunction.…”
Section: Relative Impact Of White Matter Abnormalities and Dopamine Dmentioning
confidence: 99%